Application of minimally invasive debridement for deep second-degree facial burns in the early postburn phase - Chuwei Zhang; Zihan Li; Qingrong Zhang; Ming Jiang; Zhihan Zhu; Bolin Wang; Xunrui Zhang; Xinhua Zhu; Jun Qi; Yuhui Cai; Lei Wang; Kesu Hu; et al. (BMC Surgery)
Abstract Objective This study aimed to evaluate the therapeutic efficacy of minimally invasive dermabrasion for deep second-degree facial burn wounds during the early postburn phase. Methods A total of 35 patients with deep second-degree facial burns underwent minimally invasive debridement using a hydrosurgery system within 2–4 days post-injury. Subsequently, the wounds were covered with human biological dressings. The wound infection rate, healing time, and overall healing quality following debridement were monitored. Result In this cohort of 35 patients, no infections were reported after debridement. The average healing time for these wounds was significantly shorter than that of those treated with standard surgical excision. Clinical observations indicated that minimally invasive dermabrasion was associated with a lower infection rate and reduced healing time. After 6 months, scar assessment using the Vancouver Scar Scale showed that the average score for wounds treated with minimally invasive techniques was lower than those treated with standard surgical excisional technique. Conclusions This research indicates that minimally invasive debridement during the early postburn stage can effectively reduce wound infection rates, shorten healing times, and minimize the occurrence of scar hyperplasia and contracture deformities. Therefore, minimally invasive dermabrasion is valuable in treating deep second-degree facial burn wounds.